Peran Kepala Sekolah Dalam Pengembangan Kurikulum Merdeka Belajar - Setyawati, Eny; Patimah, Siti; Subandi, Subandi; Makbulloh, Deden (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2023)
The school principal plays a crucial role in the development of the independent learning curriculum in a school. The research utilizes qualitative research with a descriptive method to understand the role of the school principal in the development of the Merdeka Belajar curriculum at SD Al Azhar 1 Bandar Lampung. Involving the school principal, teachers, and school staff as informants, the research employs in-depth interviews and participatory observation as data collection techniques. Thematic analysis is used to identify patterns, themes, and relationships that emerge. The results indicate effective leadership in overcoming challenges, implementing a student-centered curriculum, and the strategic role of the school principal in academic supervision. The success of the Merdeka Belajar curriculum at SD Al Azhar 1 Bandar Lampung depends on collaboration, open communication, and active participation of the entire school community in creating a learning environment that meets the needs of students in the era of globalization.